Psychological Capital and Innovative Work Behavior with Engagement and Job Crafting: Modal Psikologis dan Perilaku Kerja Inovatif dengan Keterlibatan dan Penciptaan Pekerjaan - Rahmi , Andriani; AlHadar , Fadhliah M.; Soleman, Marwan Man; Sabuhari, Rahmat (Indonesian Journal of Innovation Studies, 2024)
General background: Innovation is crucial for civil servants (ASN) to adapt and enhance organizational productivity. Specific background: Innovative work behavior (IWB) is essential for optimal performance, yet research often overlooks internal factors like psychological capital (PsyCap). Knowledge gap: The detailed role of PsyCap in influencing IWB, with mediators such as Employee Engagement (EE) and Job Crafting (JC), is underexplored. Aims: This study investigates the impact of PsyCap on IWB, with EE and JC as mediators, using SEM-PLS. Results: Data from 152 millennial ASNs in North Maluku show that 1) PsyCap significantly affects IWB, 2) PsyCap positively influences EE and JC, 3) EE significantly impacts IWB, while JC does not, and 4) EE partially mediates PsyCap and IWB. Novelty: Highlights the key role of EE in promoting IWB. Implications: Recommends enhancing PsyCap and EE through training and a positive organizational culture. Highlights: PsyCap significantly influences innovative work behavior among ASNs. Employee engagement acts as a partial mediator between PsyCap and IWB. Job crafting does not directly impact IWB in this study's context. Keywords: Employee Engagement, Job Crafting, Innovative Work Behavior, Millennial Staff, Psychological Capital